2020
DOI: 10.1177/1350650120945079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of grain size effect on friction and wear of nanocrystalline zirconium

Abstract: In this study, molecular dynamics simulation was conducted to investigate the frictional behaviors between diamond tool and zirconium (Zr) substrates at the nanoscale. The effects of grain size on friction and wear were discussed under different sliding velocities. The simulation results showed that the friction forces had similar variation tendencies under different sliding velocities. Besides, the friction responses were stronger at high sliding velocities because of the atomic adhesion while the ploughing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…When the sliding distance is greater than 15 nm, the friction coefficient tends to be stable. The reason for this phenomenon is that the difference in energy released by atomic bond breakage caused by the change of friction contact area [39] leads to the change of normal force and friction force, thus affecting the coefficient of friction.…”
Section: Simulation Of Friction Coefficient and Analysis Based On Two...mentioning
confidence: 99%
“…When the sliding distance is greater than 15 nm, the friction coefficient tends to be stable. The reason for this phenomenon is that the difference in energy released by atomic bond breakage caused by the change of friction contact area [39] leads to the change of normal force and friction force, thus affecting the coefficient of friction.…”
Section: Simulation Of Friction Coefficient and Analysis Based On Two...mentioning
confidence: 99%
“…In recent years, the molecular dynamics (MD) simulation approach has emerged as an important alternative in the nanomaterial field and played a significant role in the study of the microstructure and properties of materials on a molecular scale. 914 Zhu et al 15 investigate the frictional behaviors between diamond tool and zirconium (Zr) substrates at the nanoscale by MD simulation. In their study, the friction forces had similar variation tendencies under different sliding velocities.…”
Section: Introductionmentioning
confidence: 99%
“…Although nano-machining can reduce the machined surface roughness to the nanoscale, previous studies have found that defects like dislocations, cracks, and stress concentration may still occur in the workpiece during the processing. [6][7][8]20 Therefore, several methods have been proposed to improve the surface quality of the workpiece. Surface modification is the process of changing the original structure of the atoms on the workpiece, destroying the atomic structure of the workpiece before processing, causing the long-range ordered atoms on the workpiece's surface to become long-range disordered atoms, or adding a defending film to the workpiece to improve the processing surface of the workpiece.…”
Section: Introductionmentioning
confidence: 99%